Tobacco control initiatives: current scenario and SWOT (strengths, weaknesses, opportunities and threats) analysis - Shibaji Gupta; Sharmistha Sinha Gupta (Discover Public Health)
Abstract Background Tobacco use is a leading preventable cause of morbidity and mortality worldwide despite decades of global tobacco control initiatives. This study employs a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis to evaluate the current landscape of global tobacco control efforts, providing a comprehensive review of successes, challenges, and actionable opportunities Methods A narrative review was conducted using data from peer-reviewed articles, reports, and policy documents published between 2000 and 2023. Results The strengths identified include the broad implementation of the WHO’s MPOWER measures, which have resulted in notable decreases in smoking rates across various nations, as well as the proven success of plain packaging and taxation policies in curbing tobacco consumption. Weaknesses include inconsistent implementation and enforcement of these policies, especially in low- and middle-income countries, due to resource limitations and infrastructural constraints. This research identifies potential avenues for utilizing digital technologies, including social media initiatives and artificial intelligence-based cessation programmes, and promoting international cooperation to tackle the illegal tobacco trade. However, aggressive lobbying by the tobacco industry and the rise of alternative nicotine delivery systems (ENDS) are significant threats that persist. Conclusion This analysis emphasizes the need to integrate public health, policy, and community-driven efforts to achieve sustainable reductions in tobacco use. The findings aim to inform policymakers, researchers, and public health professionals, offering actionable insights to enhance the effectiveness of tobacco control programs.